The Implementation of BAN-PT Regulations Regarding Accreditation Toward An Excellent Study Program - Sholikul Hadi; Badrut Tamam; Busriyanti Busriyanti; St. Sariroh (Rechtenstudent, 2025)
Accreditation is a fundamental mechanism for evaluating the standard of higher education programs. The Constitutional Law Study Program within the Sharia Faculty at UIN Khas Jember has undertaken this process under the framework of BAN-PT, following the nine core criteria specified in BAN-PT Regulation No. 2 of 2019. This study investigates the challenges, hindrances, and potential solutions in implementing BAN-PT regulations to achieve superior accreditation status. Using an empirical legal research approach, the study collected data through interviews, direct observation, and document analysis. The accreditation process includes stages such as planning, submission, evaluation, and post-evaluation follow-up, involving various stakeholders lecturers, students, and administrative staff. Factors contributing to successful accreditation include qualified faculty, curriculum alignment, adequate infrastructure, and external partnerships. However, a significant challenge remains: limited international collaboration, which restricts access to research resources and funding. Achieving top-tier accreditation requires strategic planning, the formation of a competent accreditation drafting team, structured compliance with standards, and consistent application of the PPEPP quality cycle. Ultimately, excellent accreditation enhances institutional credibility and supports the advancement of legal education in Indonesia.